ENSURING FOOD AND ENVIRONMENTAL SECURITY IN THE DEOCCUPIED TERRITORIES IN THE CONDITIONS OF POST-WAR RECONSTRUCTION - KLYMENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Ensuring food and environmental security are important aspects of public policy and guaranteeing national security, since the provision of food products of appropriate quality, clean drinking water and an environment safe for life and health are basic in a general number of human needs and are the basis for the formation of a high level of quality of life the country’s population, ensuring its health and active longevity. In the conditions of war and post-war reconstruction, their provision becomes especially relevant for Ukraine in general and for the de-occupied territories in particular. In the conditions of the armed aggression of the Russian Federation against Ukraine, the number and scale of threats to ecological and food security have increased significantly. And the elimination of its consequences in the conditions of post-war reconstruction in the de-occupied territories will require significant resources (human, material, financial), the use of the latest technologies and the involvement of international aid, since during the hostilities catastrophic damage is caused to the surrounding natural environment. The scale of the damage caused by the armed aggression of the Russian Federation is impressive. Their elimination will require significant efforts not only on the part of Ukraine, but also the involvement of the entire democratic world community. Including international mechanisms for compensation for damage, restoration of ecological balance and agricultural production to ensure food and environmental security.